A Qualitative Study of Mothers Who Work Full-Time as Hospital Floor Nurses - Firmin, Michael W.; Lipscomb, Megan Bailey (International Journal of Advanced Nursing Studies, 2012)
We conducted qualitative interviews with a sample of 13 female floor nurses in a Midwest hospital. The women worked full-time and also had children at home for whom they provided care. The overall four results reported include particular challenges they faced in their dual-roles, including separating home from work, high stress, sleep deprivation, odd hours, and difficulty in advancing due to home life pressures. The nurses also related perceived assets and drawbacks of their profession for the given season of life. They described what they believed to be necessities for success in the dual-roles of professional nurse and care taker. Last, they related two wish-list components they desired at this point their careers as they engaged in child rearing.